Toward graphene textiles in wearable eye tracking systems for human–machine interaction - Golparvar, Ata Jedari; Yapici, Murat Kaya (Beilstein Journal of Nanotechnology, 2021)
The study of eye movements and the measurement of the resulting biopotential, referred to as electrooculography (EOG), may find increasing use in applications within the domain of activity recognition, context awareness, mobile human–computer and human–machine interaction (HCI/HMI), and personal medical devices; provided that, seamless sensing of eye activity and processing thereof is achieved by a truly wearable, low-cost, and accessible technology. The present study demonstrates an alternative to the bulky and expensive camera-based eye tracking systems and reports the development of a graphene textile-based personal assistive device for the first time. This self-contained wearable prototype comprises a headband with soft graphene textile electrodes that overcome the limitations of conventional “wet” electrodes, along with miniaturized, portable readout electronics with real-time signal processing capability that can stream data to a remote device over Bluetooth. The potential of graphene textiles in wearable eye tracking and eye-operated remote object interaction is demonstrated by controlling a mouse cursor on screen for typing with a virtual keyboard and enabling navigation of a four-wheeled robot in a maze, all utilizing five different eye motions initiated with a single channel EOG acquisition. Typing speeds of up to six characters per minute without prediction algorithms and guidance of the robot in a maze with four 180° turns were successfully achieved with perfect pattern detection accuracies of 100% and 98%, respectively.
Keywords: electrooculography (EOG); flexible electronics; graphene; human–computer interaction (HCI); human–machine interface (HMI); personal assistive device (PAD); wearable smart textile

(untitled) - ALS Association

Proceedings of the 2016 ACM International Symposium on Wearable Computers - Whitmire, E.; Trutoiu, L.; Cavin, R.; Perek, D.; Scally, B.; Phillips, J.; Patel, S. (EyeContact: scleral coil eye tracking for virtual reality, 2016)

(untitled) - Ryan, J. D.; Riggs, L.; McQuiggan, D. A. (J. Visualized Exp., 2010)

(untitled) - Pfeiffer, T.; Latoschik, M. E.; Wachsmuth, I. (J. Virtual Reality Broadcast., 2008)

(untitled) - Borghetti, D.; Bruni, A.; Fabbrini, M.; Murri, L.; Sartucci, F. (Comput. Biol. Med., 2007)

Bioelectromagnetism: Principles and Applications of Bioelectric and Biomagnetic Fields - Malmivuo, J.; Plonsey, R. (Oxford University Press, 1995)

(untitled) - Häkkinen, V.; Hirvonen, K.; Hasan, J.; Kataja, M.; Värri, A.; Loula, P.; Eskola, H. (Electroencephalogr. Clin. Neurophysiol., 1993)

Biometric Security and Privacy - Abbas, S. N.; Abo-Zahhad, M. (Eye Blinking EOG Signals as Biometrics, 2017)

(untitled) - Soundariya, R. S.; Renuga, R. (Adv. Nat. Appl. Sci., 2017)

(untitled) - Acar, G.; Ozturk, O.; Golparvar, A. J.; Elboshra, T. A.; Böhringer, K.; Yapici, M. K. (Electronics (Basel, Switz.), 2019)

(untitled) - Bissoli, A.; Lavino-Junior, D.; Sime, M.; Encarnação, L.; Bastos-Filho, T. (Sensors, 2019)

Proceedings of the Instrumentation Systems, Circuits and Transducers (INSCIT) - Lucena, S.; Conzelmann, P. (Computer USB-Mouse Emulation Using EOG, Sao Paulo, Brazil, 2019)

(untitled) - Barbara, N.; Camilleri, T. A.; Camilleri, K. P. (Biomed. Signal Process. Control, 2019)

(untitled) - Huang, Q.; Chen, Y.; Zhang, Z.; He, S.; Zhang, R.; Liu, J.; Zhang, Y.; Shao, M.; Li, Y. (J. Neural Eng., 2019)

(untitled) - Samann, F. E.; Hadi, M. S. (J. Duhok Univ., 2018)

Proceedings of the International Conference on Advances in Computing, Communications and Informatics (ICACCI) - Kumar, D.; Sharma, A. (Electrooculogram-based virtual reality game control using blink detection and gaze calibration, Jaipur, India, 2016)

Proceedings of the Computer Science and Electronic Engineering Conference (CEEC) - Valeriani, D.; Matran-Fernandez, A. (Towards a wearable device for controlling a smartphone with eye winks, Colchester, UK, 2015)

Proceedings of the International Conference on Intelligent Sensing and Information - Venkataramanan, S.; Prabhat, P.; Choudhury, S. R.; Nemade, H. B.; Sahambi, J. (Biomedical instrumentation based on electrooculogram (EOG) signal processing and application to a hospital alarm system, Chennai, India, 2005)

(untitled) - Chang, W.-D.; Cha, H.-S.; Kim, D. Y.; Kim, S. H.; Im, C.-H. (J. NeuroEng. Rehabil., 2017)

(untitled) - Golparvar, A. J.; Yapici, M. K. (IEEE Sens. J., 2018)

(untitled) - Homayounfar, S. Z.; Rostaminia, S.; Kiaghadi, A.; Chen, X.; Alexander, E. T.; Ganesan, D.; Andrew, T. L. (Matter, 2020)

Proceedings of the IEEE Sensors Conferenc - Golparvar, A.; Yapici, M. K. (Wearable graphene textile-enabled EOG sensing, 2017)

(untitled) - Yapici, M. K.; Alkhidir, T.; Samad, Y. A.; Liao, K. (Sens. Actuators, B, 2015)

(untitled) - Yapici, M. K.; Golparvar, A. (Wearable graphene textile-based electro-ocular monitoring and object interaction system, 2020)

(untitled) - Golparvar, A. J.; Yapici, M. K. (J. Electrochem. Soc., 2019)

Computers Helping People with Special Needs - Saif, M. B.; Felzer, T. (Replacement of the Standard Computer Keyboard and Mouse by Eye Blinks, 2016)

Proceedings of the Symposium on Eye tracking research & applications - MacKenzie, I. S.; Zhang, X. (Eye typing using word and letter prediction and a fixation algorithm, Georgia, U.S., 2008)

(untitled) - Tang, Y.; Zhou, H.; Sun, X.; Diao, N.; Wang, J.; Zhang, B.; Qin, C.; Liang, E.; Mao, Y. (Adv. Funct. Mater., 2020)

(untitled) - Zhang, B.; Tang, Y.; Dai, R.; Wang, H.; Sun, X.; Qin, C.; Pan, Z.; Liang, E.; Mao, Y. (Nano Energy, 2019)

(untitled) - Cui, X.; Zhao, T.; Yang, S.; Xie, G.; Zhang, Z.; Zhang, Y.; Sang, S.; Lin, Z.-H.; Zhang, W.; Zhang, H. (Nano Energy, 2020)

(untitled) - Guo, R.; Zhang, H.; Cao, S.; Cui, X.; Yan, Z.; Sang, S. (Mater. Des., 2019)

(untitled) - Zhu, M.; Lou, M.; Yu, J.; Li, Z.; Ding, B. (Nano Energy, 2020)

(untitled) - Zhu, M.; Lou, M.; Abdalla, I.; Yu, J.; Li, Z.; Ding, B. (Nano Energy, 2020)

(untitled) - Lou, M.; Abdalla, I.; Zhu, M.; Wei, X.; Yu, J.; Li, Z.; Ding, B. (ACS Appl. Mater. Interfaces, 2020)